Hoosier Sport: a research protocol for a multilevel physical activity-based intervention in rural Indiana - Greeven, Sarah J.; Fernández Solá, Paola A.; (Martinez) Kercher, Vanessa M.; Coble, Cassandra J.; Pope, Katherine J.; Erinosho, Temitope O.; Grube, Aidrik; Evanovich, Justin M.; Werner, Nicole E.; Kercher, Kyle A. (Frontiers in Public Health, 2023)
Introduction Currently, only 1 in 4 children in the U.S. engage in the recommended amount of physical activity (PA) and disparities in PA participation increase as income inequities increase. Moreover, leading health organizations have identified rural health as a critical area of need for programming, research, and policy. Thus, there is a critical need for the development and testing of evidence-based PA interventions that have the potential to be scalable to improve health disparities in children from under-resourced rural backgrounds. As such, the present study utilizes human-centered design, a technique that puts community stakeholders at the center of the intervention development process, to increase our specific understanding about how the PA-based needs of children from rural communities manifest themselves in context, at the level of detail needed to make intervention design decisions. The present study connects the first two stages of the NIH Stage Model for Behavioral Intervention Development with a promising conceptual foundation and potentially sustainable college student mentor implementation strategy. Methods We will conduct a three-phase study utilizing human-centered community-based participatory research (CBPR) in three aims: (Aim 1) conduct a CBPR needs assessment with middle school students, parents, and teachers/administrators to identify perceptions, attributes, barriers, and facilitators of PA that are responsive to the community context and preferences; (Aim 2) co-design with children and adults to develop a prototype multi-level PA intervention protocol called Hoosier Sport; (Aim 3) assess Hoosier Sport’s trial- and intervention-related feasibility indicators. The conceptual foundation of this study is built on three complementary theoretical elements: (1) Basic Psychological Needs mini-theory within Self-Determination Theory; (2) the Biopsychosocial Model; and (3) the multilevel Research Framework from the National Institute on Minority Health and Health Disparities. Discussion Our CBPR protocol takes a human-centered approach to integrating the first two stages of the NIH Stage Model with a potentially sustainable college student mentor implementation strategy. This multidisciplinary approach can be used by researchers pursuing multilevel PA-based intervention development for children.